Modernization of the analytical nuclear-physical complex sokil - Karpus, S.G.; Kuzmenko, V.V.; Levenets, V.V.; Lonin, O.Yu.; Omelnik, A.P.; Shchur, A.O.; Sukhostavets, V.I. (Problems of Atomic Science and Technology, 2023)
New modifications that have been used at the analytical nuclear-physics complex (ANPC) Sokil in recent years are described. They concerned an ion accelerator with an increase in the energy of accelerated ions and the separation of ⁴He²⁺ and H²⁺ beams. A system for irradiating materials science samples with a beam of gas ions with the possibility of choosing the irradiated target space has been created. The use of electrostatic beam deflection made it possible to increase the service life of the foil for beam release into the atmosphere. The use of a pyrocarbon filter in the analysis of monoelements or objects with a high X-ray output of one or several elements changed the form of the spectrum. These modifications made it possible to improve the operation of the complex and obtain new possibilities in solving problems by analytical nuclear physics methods in the study of materials for nuclear power engineering and ecology. Описано нові модифікації, які застосовувалися на аналітичному ядерно-фізичному комплексі Сокіл в останні роки. Вони стосувалися прискорювача іонів зі збільшенням енергії прискорених іонів і розділенням пучків ⁴He²⁺ і H²⁺. Створено систему опромінення матеріалознавчих зразків пучком іонів газу із можливістю вибору опромінюваного простору мішені. Використання електростатичного відхилення променя дозволило збільшити термін служби фольги для виходу променя в атмосферу. Використання піровуглецевого фільтра при аналізі моноелементів або об’єктів з високим рентгенівським випромінюванням одного або кількох елементів змінило форму спектра. Ці модифікації дозволили удосконалити роботу комплексу та отримати нові можливості вирішення задач аналітичними методами ядерної фізики при дослідженні матеріалів для атомної енергетики та екології.